Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek
Wydawnictwo:Nowa Era
Rok wydania:2015
Rozwiąż równanie 4.25 gwiazdek na podstawie 8 opinii

`a)\ 3(2x-7)-(7x-13)=-10` 

` \ \ \ 6x-21-7x+13=-10` 

`\ \ \ -x-8=-10\ \ \ |+8` 

`\ \ \ -x=-2\ \ \ |*(-1)` 

`\ \ \ x=2` 

 

 

`b)\ -2(-27-3x)=-3(2x-10)` 

`\ \ \ 54+6x=-6x+30\ \ \ \|+6x` 

`\ \ \ 54+12x=30\ \ \ |-54` 

`\ \ \ 12x=-24\ \ \ |:12` 

`\ \ \ x=-2` 

 

 

`c)\ 6-2(2x-1/2)=4x-2(3/4-3x)\ \ \ |:2` 

`\ \ \ 3-(2x-1/2)=2x-(3/4-3x)` 

`\ \ \ 3-2x+1/2=2x-3/4+3x\ \ \ \|*4` 

`\ \ \ 12-8x+2=8x-3+12x` 

`\ \ \ 14-8x=20x-3\ \ \ |+8x` 

`\ \ \ 14=28x-3\ \ \ |+3` 

`\ \ \ 28x=17\ \ \ |:28` 

`\ \ \ x=17/28` 

 

 

`d)\ 3x=x-(1-(x-3))` 

`\ \ \ 3x=x-(1-x+3)` 

`\ \ \ 3x=x-(4-x)` 

`\ \ \ 3x=x-4+x` 

` \ \ \ 3x=2x-4\ \ \ |-2x` 

`\ \ \ x=-4` 

 

 

`e)\ 5x-(2x+(3-x))=11` 

`\ \ \ 5x-(2x+3-x)=11` 

`\ \ \ 5x-(x+3)=11` 

`\ \ \ 5x-x-3=11` 

`\ \ \ 4x-3=11\ \ \ |+3` 

`\ \ \ 4x=14\ \ \ |:4` 

`\ \ \ x=14/4=7/2=3 1/2` 

 

 

`f)\ 1-(x-(x-(x-1)))=0` 

` \ \ \ 1-(x-(x-x+1))=0` 

`\ \ \ 1-(x-1)=0` 

`\ \ \ 1-x+1=0` 

`\ \ \ 2-x=0\ \ \ |+x` 

` \ \ \ x=2`